Spremljanje trenutne frekvenčne vsebine pri zagonu pralnega stroja - Simonovski, Igor (Strojniški vestnik, 2001)
The Fourier integral transform is a very useful tool for analyzing the frequency content of steady processes. When dealing with non-stationary processes, however, other methods for determining the frequency content must be applied. This paper deals with the windowed Fourier transform and, the more recent wavelet transform. The windowed Fourier transform uses basic functions that have an unlimited definition range and requires multiplication of the observed process with a time-limited window function to be able to detect local non-stationarities. The wavelet transform uses basic functions that have a limited definition range for the some purpose. In this paper we compare the ability of the windowed Fourier transform and the continuous wavelet transform to monitor the frequency content of a non-stationary process-washing machine startup.The results show that the windowed Fourier transform values only makes it possible to roughly determine the instantaneous drum-spin frequency band. Using the continous wavelet transform we were able to determine the instantaneous drum-spin frequency more accurately.
Keywords: procesi neustaljeni; transformacije Fourierjeve okenske; transformacije valčne zvezne; valčki Gaborjevi; stroji pralni; neustaljeni procesi; frekvenčna analiza; Fourierova transformacija; valčna transformacija; pralni stroji